Ephemeral Emblem: Jacques-Louis David and the Making of a Revolutionary Martyr - Berman, Daniella (Status Quaestionis, 2025)
In December 1793, Maximilien Robespierre raised a virtually unknown child martyr, Joseph Bara, to cult status through Jacobin rhetoric. The painter Jacques-Louis David was tasked with both producing a commemorative portrait and organizing a Pantheonization ceremony. The resulting enigmatic canvas–more emblem than portrait–offers new modes of understanding David’s Revolutionary-era project and the contingent nature of artistic production during a turbulent era. Often considered unfinished, this painting’s materiality is reflective of the ceremony to which it is fundamentally linked. This article argues that both the Revolutionary fête and David’s newfound visual language should be understood as modes of ephemeral performance that cast the spectator as a co-maker of meaning, and that the painting does not represent the death of an individual figure but allegorically commemorates the unrealized ceremony. This article thus demonstrates the ways that the Revolution’s contingency manifested itself materially and conceptually in the arts.